The Europeanisation Process and the Pre-Accession Dynamics in Romania - Teodor Lucian Moga; Diana Onu (CES Working Papers, 2011)
In recent years a substantial part of literature that covers topics on European integration has turned its attention to how the membership of the European Union (EU) has generated and contributed to domestic reform, a process commonly known as Europeanisation. This process represents the reform of institutions, structures and policies in compliance with the requirements, policies and dynamics of the European integration mechanisms. Following the national - European interaction, countries internalise European legislation and adapt institutionally. The purpose of this paper is to analyse the Europeanisation process and also to what extent it has influenced the political and economic reform in Romania throughout the pre-accession period. Despite its essential contributions, the Europeanisation effects were less significant in Romania (especially in the early years of negotiations with Brussels) compared with other Eastern European countries. And this has not been caused by the Europeanisation lack of efficiency, but mainly because of the Romanian political class reluctant to change that largely undermined the dynamics of the accession process.
Keywords: 330; European Union; Europeanisation process; EU membership; Romania